Postoperative liver regeneration does not elicit recurrence of colorectal cancer liver metastases after major hepatectomy - Hamm, Alexander; Hidding, Sarah; Mokry, Theresa; Radeleff, Boris; Mehrabi, Arianeb; Büchler, Markus W.; Schneider, Martin; Schmidt, Thomas (Surgical oncology, 2020)
Background and objectives - Recurrence is a frequent concern in curatively resected CRC liver metastases. Translational research suggests that regeneration upon hepatectomy may also alleviate metastatic recurrence; however, the significance in patients is unclear. We therefore sought to study the effect of liver regeneration on tumor recurrence in patients. - Methods - In this retrospective cohort study, we included 58 out of 186 potentially eligible patients from our prospectively maintained database of CRC liver metastasis patients between 2001 and 2012 with a median follow-up of 42 months who underwent a formal right or left hemihepatectomy. Liver regeneration in CT volumetry was correlated with recurrence of CRC liver metastases and overall survival. - Results - Liver regeneration increased up to 14 months to 21.0% for left and 122.6% for right hemihepatectomy, respectively, with comparable final volumes. Regeneration was independent of initial tumor stage, number of metastases, and preoperative chemotherapy. Patients with lower liver regeneration showed earlier recurrence of CRC liver metastases (p = 0.006). Overall survival did not differ in patients with weak versus strong liver regeneration. - Conclusions - The extent of liver regeneration after major hepatectomy does not impede overall survival. Therefore, our data encourage aggressive therapeutical regimes for CRC liver metastases involving major hepatectomies as part of a curative approach.
Gesehen am 25.01.2021